Exposure of female mice to perfluorooctanoic acid suppresses hypothalamic kisspeptin‐reproductive endocrine system through enhanced hepatic fibroblast growth factor 21 synthesis, leading to ovulation failure and prolonged dioestrus. (19th April 2020) - Zhang, Yajie; Cao, Xinyuan; Chen, Lin; Qin, Yaoyao; Xu, Ye; Tian, Ying; Chen, Ling
Abstract: Perfluorooctanoic acid (PFOA) is widely used in household applications. High‐dose exposure to PFOA has been associated with increased risks of infertility and premature ovarian insufficiency in woman. PFOA can alter hepatic gene expression by activating peroxisome proliferator‐activated receptor α (PPARα). The present study investigated whether exposure to PFOA via PPARα activation alters the synthesis of hepatic fibroblast growth factor 21 (FGF21) to disturb female neuroendocrine and reproductive function. In the present study, we show that the oral administration of PFOA (2 or 5 mg kg ‐1 ) in adult female mice (PFOA mice) caused prolonged dioestrous, a reduction in the number of corpora lutea and decreased levels of hypothalamic gonadotrophin‐releasing hormone, serum progesterone and luteinising hormone (LH). Exposure to PFOA decreased the expression of vasopressin in the suprachiasmatic nucleus (SCN) and kisspeptin in the anteroventral periventricular nucleus (AVPV) with deficits in preovulation or oestrogen‐induced LH surge. PFOA via activation of PPARα increased dose‐dependently hepatic FGF21 expression, leading to elevated serum and hypothalamic FGF21 concentrations. Treatment of PFOA mice with the PPARα antagonist GW6471 or the FGF21 inhibitor PD173074 rescued SCN vasopressin and AVPV‐kisspeptin expression. Either administration of GW6471 and PD173074 or treatment with vasopressin and the G protein coupled receptor 54 agonist kisspeptin‐10 in PFOA‐mice was able to recover the regular oestrous cycle, ovulation ability, LH surge production and reproductive hormone levels. The present study provides in vivo evidence that exposure to PFOA (≥2 mg kg ‐1 ) in mice causes down‐regulation of the kisspeptin‐reproductive endocrine system by enhancing PPARα‐mediated hepatic FGF21 expression. The liver‐brain reproductive endocrine disorder caused by PFOA exposure may lead to prolonged dioestrous and ovulation failure.